Perubahan Miskonsepsi Siswa pada Perkuliahan Evolusi Melalui Dual Situated Learning Model - Adri, Helmia Tasti; Rustaman, Nuryani Y; Tapilouw, Fransisca Sudargo; Hidayat, Topik (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
This research departs from the many found misconceptions experienced by students in evolutionary lectures. So it is very important to make improvements. The efforts carried out in this study were to improve students' misconceptions through the use of Dual situated learning model as a model of change in conception based on the criteria considered to be very capable of correcting problems. The study was conducted at a public university in Bandung in the department of biology with 33 respondents as the subject of research. To find out the success of the activities carried out, data was taken using the Certainty of response index test. The results found are that there is a significant effect of Dual Situated Learning Model usage on the level of change in student misconception.